2000
DOI: 10.1523/jneurosci.20-18-07067.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Neuronal Modulation Alters Dopamine D2Receptor Availability In Vivo by Regulating Receptor Affinity Induced by Facilitated Synaptic Dopamine Turnover: Positron Emission Tomography Studies with Microdialysis in the Conscious Monkey Brain

Abstract: To evaluate the cholinergic and dopaminergic neuronal interaction in the striatum, the effects of scopolamine, a muscarinic cholinergic antagonist, on the striatal dopaminergic system were evaluated multi-parametrically in the conscious monkey brain using high-resolution positron emission tomography in combination with microdialysis. L-3,4-Dihydroxyphenylalanine (L-[␤-11 C]DOPA) and 2␤-carbomethoxy-3␤-(4-fluorophenyl)-tropane ([␤-11 C]CFT) were used to measure dopamine synthesis rate and dopamine transporter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…Administration of drugs (such as nicotine) that do increase DA cell firing and DA synaptic concentration without blocking the DAT are associated with reduced [ 11 C]raclopride binding in the absence of detectable changes in extracellular DA measured with microdialysis (Kim et al, 1998;Tsukada et al, 1999aTsukada et al, , b, 2000. The reason for this apparent discrepancy is that the DAT are effective at preventing the diffusion of synaptic DA to the extracellular space (Tsukada et al, 2000). Thus, [ 11 C]raclopride imaging provides a more direct measure of D 2 receptor stimulation by DA than microdialysis (see, for further discussion, Laruelle, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of drugs (such as nicotine) that do increase DA cell firing and DA synaptic concentration without blocking the DAT are associated with reduced [ 11 C]raclopride binding in the absence of detectable changes in extracellular DA measured with microdialysis (Kim et al, 1998;Tsukada et al, 1999aTsukada et al, , b, 2000. The reason for this apparent discrepancy is that the DAT are effective at preventing the diffusion of synaptic DA to the extracellular space (Tsukada et al, 2000). Thus, [ 11 C]raclopride imaging provides a more direct measure of D 2 receptor stimulation by DA than microdialysis (see, for further discussion, Laruelle, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for reduced binding in PFC might be competition between [ 11 C]FLB457 and synaptic DA enhanced by NMDA inhibition based upon a conventional 'occupancy' theory. This is unlikely, however, because Okauchi et al (2001) previously reported that methamphetamine did not affect [ 11 C]FLB457 binding to extrastriatal D 2 R, suggesting the insensitivity of [ 11 C]FLB457 for synaptic DA, probably because of its high affinity to D 2 R. Instead of the conventional 'occupancy' theory, another explanation may be a 'rate' theory defined as the dynamics of DA binding to receptors and the synaptic turnover of DA (Tsukada et al, 1999a(Tsukada et al, , 2000a. Further studies are needed on the modulation of [ 11 C]FLB457 binding to extrastriatal D 2 R. In contrast to D 2 R, no significant changes in [ 11 C]NNC112 binding to PFC D 1 R were detected in the acute study.…”
Section: Prefrontal Cortical Da Receptor Changes Measured By Petmentioning
confidence: 99%
“…18 F-FDOPA uptake reflects the activity of aromatic L-amino acid decarboxylase (AADC) in the nerve terminals of the nigrostriatal dopaminergic pathway, and the metabolized 18 F-fruoro-dopamine ( 18 F-FDA) is stored in the vesicles through vesicular monoamine transporter. We have applied b-11 C-L-DOPA (5) to monitor dopamine synthesis rate facilitated by pharmacologic manipulations in normal monkeys (6,8,9) as well as impaired (10) in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated PD model monkeys (11). Because these research studies required multiparametric PET assessments of presynaptic dopamine synthesis, DAT, and postsynaptic dopamine receptors in the same subject in a day, the short half-life of 11 C is very useful for the repeated PET measurements.…”
mentioning
confidence: 99%